Theorizing China-world integration: sociospatial reconfigurations and the modern silk roads - Mayer, Maximilian; Zhang, Xin (2020)
This paper develops a spatial perspective to examine the nature of China’s transnational influence, focusing on the implications of the Belt and Road Initiative (BRI) for international relations. Drawing upon political economy, regional studies and critical geopolitics, we argue that the most interesting puzzle concerning the BRI pertains to the ongoing reconfigurations of political space. Contemporary sociospatial reconfigurations as analyzed through a multidimensional framework offer key insights into the operations and the extent of China’s growing global power in general and with respect to the BRI in particular. We draw on a broad range of materials such as maps, Chinese academic and policy discourse as well as observations about corridor projects to theorize a) how the spatiality of global and regional connectivity is reconfigured through the process of China’s integration with the world; and b) how corridorization as a dominant physical and ideational process shapes Chinese investment projects and reconfigures state spatiality along the BRI. The results indicate that the main territorial pattern is not the nation or the region but the corridor. Furthermore, expansionist and unidirectional stories of China’s growing power overlook the local encounters and negotiations necessary for infrastructure projects to succeed. In addition, China’s economic statecraft is contextualized within the ongoing post-financial crisis political-economic restructuring of territories, places, and scales within the global capitalist system.